Transconstitucionalismo como medida para efetivação de direitos das pessoas presas : uma abordagem do Estado de Coisas Inconstitucional no sistema prisional brasileiro - Souza, Andressa Rita Alves de (2023)
Given the crisis scenario of the brazilian prison system, marked by massive violations of fundamental rights and human dignity, it is necessary to think of legal measures to protect the incarcerated person. Thus, the present work aimed to develop a study on transconstitutionalism as a measure for the realization of rights of the prisoner, considering that it is a theory based on the dialogical construction between legal orders for better problem solving legal and constitutional problems. In view of this, the study addressed the theoretical conceptions developed by Marcelo Neves about transconstitutionalism, having as its central object of analysis the State of Things Unconstitutional in the brazilian prison system, because this legal mechanism was previously used in another Constitutional Court, being, therefore, a case of constitutional conversation between courts. The work was structured in three thematic chaptersThe first point addressed theoretical and historical constructions on constitutionalism, transconstitutionalism and constitutional jurisdiction for the protection of fundamental rights and human dignity. The second part developed about the vulnerability of the prisoner in the face of inefficient protection by the State, arguing the previous and intensified vulnerability within the prisons, in order to highlight the scenario of violations and omissions within the prison. In a third moment, it dealt with the Unconstitutional State of Things, listing its conceptualization and its application assumptions, as well as the Colombian and Brazilian decisions. Finally, it was highlighted about the brazilian decision in ADPF 347, discussing the constitutional conversation of the ECI as a measure of transconstitutionalism for the realization of the rights of prisoners. The work, of a qualitative character, used bibliographic and jurisprudential research, with a deductive study method.